2007
DOI: 10.1186/gb-2007-8-7-r129
|View full text |Cite
|
Sign up to set email alerts
|

FlyMine: an integrated database for Drosophila and Anopheles genomics

Abstract: FlyMine is a data warehouse that addresses one of the important challenges of modern biology: how to integrate and make use of the diversity and volume of current biological data. Its main focus is genomic and proteomics data for Drosophila and other insects. It provides web access to integrated data at a number of different levels, from simple browsing to construction of complex queries, which can be executed on either single items or lists. RationaleWith the completion of increasing numbers of genome sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
403
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 366 publications
(411 citation statements)
references
References 69 publications
5
403
0
Order By: Relevance
“…Significance was calculated with standard Fisher's exact tests on contingency tables with counts of genes displaying differential expression. Analyses of enrichment in gene ontology categories were performed with standard methods as previously implemented (Branco et al 2013) and confirmed with the FlyMine platform (Lyne et al 2007). …”
mentioning
confidence: 99%
“…Significance was calculated with standard Fisher's exact tests on contingency tables with counts of genes displaying differential expression. Analyses of enrichment in gene ontology categories were performed with standard methods as previously implemented (Branco et al 2013) and confirmed with the FlyMine platform (Lyne et al 2007). …”
mentioning
confidence: 99%
“…Tissue specificity of differentially expressed genes was assessed as previously described (Branco et al, 2013) using the FlyAtlas resource (Chintapalli et al, 2007). Discovery of gene ontology enrichments were done with the FlyMine platform and enrichment P-values corrected with Holm-Bonferroni (Lyne et al, 2007).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The number of MADF, BESS, and MADF-BESS domains were counted in different species in the animal kingdom based on information available in databases such as InterPro (Hunter et al 2012), UniProt (Magrane and Consortium 2011), Flybase (Marygold et al 2013), Flymine (Lyne et al 2007), SMART (Schultz et al 1998), 12 Drosophila genomes (Clark et al 2007), and ORTHODB (Waterhouse et al 2013). MADF-BESS domain protein sequences were downloaded from UniProt.…”
Section: Bioinformatics Analysismentioning
confidence: 99%